2016
DOI: 10.1093/bja/aev349
|View full text |Cite
|
Sign up to set email alerts
|

A rational approach to fluid therapy in sepsis

Abstract: Aggressive fluid resuscitation to achieve a central venous pressure (CVP) greater than 8 mm Hg has been promoted as the standard of care, in the management of patients with severe sepsis and septic shock. However recent clinical trials have demonstrated that this approach does not improve the outcome of patients with severe sepsis and septic shock. Pathophysiologically, sepsis is characterized by vasoplegia with loss of arterial tone, venodilation with sequestration of blood in the unstressed blood compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
174
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(186 citation statements)
references
References 152 publications
(85 reference statements)
1
174
0
11
Order By: Relevance
“…Fluid resuscitation exerts its potentially therapeutic effect by increasing the stressed volume of the circulation leading to increased venous return and cardiac output [59]. Recently, attempts have been made to quantify the potency of fluid administration to achieve this in sepsis.…”
Section: Changing Understanding Of Sepsis and Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid resuscitation exerts its potentially therapeutic effect by increasing the stressed volume of the circulation leading to increased venous return and cardiac output [59]. Recently, attempts have been made to quantify the potency of fluid administration to achieve this in sepsis.…”
Section: Changing Understanding Of Sepsis and Resuscitationmentioning
confidence: 99%
“…Studies in healthy individuals show increases in blood volume of 25–30% immediately after administration with 10–15% persisting 4 h after the infusion [60]. However, sepsis is known to produce changes in vascular permeability and the glycocalyx structure that may decrease the retention of fluids in the vascular compartment [59]. In an animal model of sepsis and fluid bolus resuscitation, only 0.6% of the fluid bolus remained in the circulation after 20 min [61].…”
Section: Changing Understanding Of Sepsis and Resuscitationmentioning
confidence: 99%
“…The collective failure of these trials casts doubt on the notion of maladaptive dysregulation in sepsis. They also raise questions about the assumption of inadequate tissue oxygen and perfusion in septic shock, an idea that itself has been criticized [39].…”
Section: Sepsis Bundles and Early Goal Directed Therapymentioning
confidence: 99%
“…However, in the nearly two decades since the influential Rivers trial, EGDT has been shown to be ineffective, and the current SSC bundles rest on a thin evidence base, reviewed in [39].…”
Section: Sepsis Bundles and Early Goal Directed Therapymentioning
confidence: 99%
See 1 more Smart Citation